The clash of fundamentalisms : crusades, jihads and modernity - Ali, Tariq (London : Verso, 2003)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: terrorisme; imperialisme; Midden-Oosten.; Verenigde Staten van Amerika